SOSIALISASI PENGUATAN MOTIVASI BELAJAR UNTUK MENCETAK GENERASI UNGGUL DI SMK NURUL HUDA BAROS - Haryono, Riki; Winaldo, Jepri; Octaviani, Rani; Febrianti, Empin; Setiawan, Farhan Nanda (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Community service is one of the tangible manifestations of the role of universities in making a positive contribution to the surrounding environment. One of the important aspects of human resource development is learning motivation, because motivation plays a big role in determining the achievements and readiness of the younger generation to face future challenges. This program carries the activity